Suppression Efficiency for Dust from an Iron Ore Pile Using a Conventional Sprinkler and a Water Mist Generator - Yen-Yi Lee; Chung-Shin Yuan; Po-Hsuan Yen; Justus Kavita Mutuku; Chien-Er Huang; Chih-Cheng Wu; Po-Jen Huang (Aerosol and Air Quality Research)
Abstract Re-suspension of iron ore dust presents a constant hazard in the working environment within steel production plants. Herein, the optimal operating parameters for maximum dust suppression efficiencies through a water mist generator and a conventional sprinkler for particulate matter (PM) originating from an iron ore pile measuring about 2 m in height and with a stacking angle of about 30° are investigated. The effects of operating parameters including wind velocity, spray angle, and mode of water supply on dust suppression efficiencies are evaluated. Size differentiated PM samples were collected from the upwind and downwind locations of the iron oral pile and the dust suppression efficiencies are determined. The operating parameters with the highest dust suppression efficiencies using the water mist technology are low spray angle, low wind velocity, and intermittent water supply, while those for water sprinkling technology are high spray angle, low wind velocity, and intermittent water supply. The average dust suppression efficiencies for Total Suspended Particles (TSP), PM10, and PM2.5 for the mist generators are 80.9%, 77.9%, and 76.9%, respectively, whereas those for the conventional sprinklers are 76.4%, 72.9%, and 72.7%, respectively. For the surfactant to water ratios of 0.024, 0.022 and no surfactant, the ratio of 0.024 had the highest dust suppression efficiencies for TSP, PM10, and PM2.5 at 90.9%, 89.5%, and 89.0%, respectively. Insights from this investigation can be applied to optimize the dust suppression methods to ensure economical consumption of water and energy.